2009
DOI: 10.1016/j.jfa.2009.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Quantum group of orientation-preserving Riemannian isometries

Abstract: We formulate a quantum group analogue of the group of orientation-preserving Riemannian isometries of a compact Riemannian spin manifold, more generally, of a (possibly R-twisted and of compact type) spectral triple. The main advantage of this formulation, which is directly in terms of the Dirac operator, is that it does not need the existence of any 'good' Laplacian as in our previous works on quantum isometry groups. Several interesting examples, including those coming from Rieffel-type deformation as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
133
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(135 citation statements)
references
References 35 publications
2
133
0
Order By: Relevance
“…One is now confronted with two possible notions of quantum isometry: the global one of [12] and the infinitesimal one of [4]. They are only conjecturally equivalent, with the global notion being weaker.…”
Section: Introductionmentioning
confidence: 99%
“…One is now confronted with two possible notions of quantum isometry: the global one of [12] and the infinitesimal one of [4]. They are only conjecturally equivalent, with the global notion being weaker.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, especially in the mathematical physics literature, the focus seems to be on investigating spectral triples on deformations of function algebras of classical spaces. In the recent work of Goswami and the first named author [3][4][5], the notion of a quantum isometry group of a spectral triple, understood as the universal compact quantum group acting on the corresponding noncommutative manifold in a way compatible with the spectral triple structure was introduced. It was shown that if the spectral triple is sufficiently well behaved, the quantum isometry group exists, and in the classical situation the definition of 'compatible' actions given in [3] describes precisely the relevant group actions preserving the Riemannian metric.…”
Section: Introductionmentioning
confidence: 99%
“…We begin by introducing basic notations and recalling the construction of spectral triples on group C * -algebras associated to a length function on the group. In Section 2 we describe the approach to the quantum group of orientation preserving isometries due to Goswami and the first named author, and show that the triples described in Section 1 fit in the framework studied in [4]. The first concrete examples appear in Section 3 and come from singly generated abelian groups.…”
Section: Introductionmentioning
confidence: 99%
“…Computations of these compact quantum groups were done for several examples, including the tori, spheres, Podleś quantum spheres, and Rieffel deformations of compact Riemannian spin manifolds. For these studies we refer to [6,7,8,9, 10] and references therein. The finite noncommutative geometry F = (A F , H F , D F , γ F , J F ) describing the internal space of the Standard Model is given by a unital real spectral triple over the finite-dimensional real…”
Section: Introductionmentioning
confidence: 99%
“…These are compact quantum groups in the sense of Woronowicz [41]. The notion of compact quantum symmetries for "continuous" mathematical structures, like commutative and noncommutative manifolds (spectral triples), first appeared in [28], where quantum isometry groups were defined in terms of a Laplacian, followed by the definition of "quantum groups of orientation preserving isometries" based on the theory of spectral triples in [7], and on spectral triples with a real structure in [29]. Computations of these compact quantum groups were done for several examples, including the tori, spheres, Podleś quantum spheres, and Rieffel deformations of compact Riemannian spin manifolds.…”
mentioning
confidence: 99%